Chapter Tipologie amministrative della signoria in Italia fra medioevo ed età moderna - CAROCCI, Alessandro (Reti Medievali E-Book, 2021)
Lordship management is a broad subject scarcely treated by historians; even when analysed, it has never been the object of exhaustive reconstructions and systematic surveys. The article provides a first, provisional overview of the main forms of lordship administration that changed depending on the period, region, lordship, type of revenue and many other factors. The Weberian notion of ideal type is particularly helpful in order to try to master the multiplicity and variety of forms of administration used in practice. On its basis, the essay identifies two basic ideal types, 'Direct Management' and 'Indirect Management', which are in turn divided into five sub-ideal types. Lastly, it questions the economic and social effects of each form of management, and the possibility of identifying, depending on the period and region, a more or less extensive diffusion of lordships attributable to the different ideal types.